Evaluation of alternative monomers to HEMA for dental applications. Issue 7 (July 2017) - Tauscher, Sven; Angermann, Jörg; Catel, Yohann; Moszner, Norbert
Highlights: Nine monomers are evaluated as alternatives to HEMA in dental materials. Photopolymerization kinetics of these monomers are investigated by photo-DSC. Some of the tested monomers are promising candidates to replace HEMA in luting composites and self-etch adhesives. Abstract: Objective: The objective of this work is to find potential alternative monomers to 2-hydroxyethyl methacrylate (HEMA) for dental materials (self-etch adhesives and luting composites). Methods: Monomers1–9 were tested as potential HEMA substitutes. Methacrylates4, 5 and6 and ( N -methyl)acrylamides7–9 were synthesized and characterized by 1 H NMR spectroscopy. The reactivity of each monomer was studied using photo-DSC. Mixtures of monomers1–9 with the urethane dimethacrylate UDMA (1/1: wt/wt) were formulated and cured. The water sorption and solubility of these materials were determined according to ISO 4049. Luting composites based on monomers1–9 or on HEMA were formulated. The flexural strength and modulus of elasticity were measured using a three-point bending setup, according to ISO 4049. Self-etch adhesives containing monomers1–9 or HEMA were prepared and used to mediate a bond between the dental composite Tetric EvoCeram ® and both dentin and enamel. The shear bond strength (SBS) was measured using a Zwick universal testing machine. Results: Polymerizable diols3 and4 as well as ( N -methyl)acrylamides7–9 were found to be significantly more reactive than HEMA. Resins based on the hydrophilic monomers3, 7 and8 exhibited a significantly higher water sorption than the corresponding HEMA-containing material. Luting composites containing monomers2, 3, 6 and7 showed similar or even improved mechanical properties compared to the reference material containing HEMA. Self-etch adhesives containing monomers4 and9 provided significantly higher dentin SBS than the reference material. Significance: Some of the evaluated monomers are promising candidates for the development of HEMA-free dental materials.